The Degree of Inclusion of Green Chemistry Principles in Chemistry Textbooks for Ninth and Tenth Grades in Jordan - Alebous, Tahani Mohammad Nahar (Dirasat: Educational Sciences, 2025)
Objectives: The study aimed to examine the degree to which green chemistry principles are included in chemistry textbooks for the 9th and 10th grades in Jordan, and to identify the differences in the level of inclusion based on the grade level variable (ninth & tenth). Methods: The descriptive-analytical method was used, with a content analysis form consisting of 72 items, distributed across the twelve principles of green chemistry. The chemistry textbooks for the 9th and 10th grades in Jordan were analyzed according to the tool. The validity and reliability of the tool were verified. Results: The results showed that the frequency of green chemistry principles was highest in the 9th-grade chemistry textbook, with a frequency of 71, which corresponds to 35.5%. This was followed by the 10th-grade chemistry textbook, which had a frequency of 37, or 19.17%. The results also showed statistically significant differences in the degree of inclusion of green chemistry principles in the textbooks, attributed to the grade level variable. Conclusion: In light of the study’s results, it is recommended that the content of chemistry textbooks be reviewed and that topics, activities, and educational situations focusing on green chemistry principles be included in the content of science and chemistry textbooks at all educational stages.